Effects of the intensity of interval training on aerobic fitness, body composition and resting metabolic rate of women with overweight or obesity: A randomized trial - Andreato L.V.* (2023)
© 2023 – IOS Press. All rights reserved.BACKGROUND: Moderate-intensity interval training (MIIT) may be a viable exercise format for improving body composition, aerobic fitness, and health-related variables. OBJECTIVES: This randomized trial aimed to analyze the effect of MIIT or high-intensity interval training (HIIT) on aerobic fitness, body composition variables, and resting metabolic rate (RMR) in women with overweight or obesity. METHODS: 31 sedentary adult women with overweight or obesity performed 7 weeks × 3 weekly sessions of either HIIT or MIIT. Physical and physiological tests were applied before and after training. RESULTS: In both analyses (intention-to-treat and by adherence to the training), aerobic fitness showed a time effect (p = 0.041 and p = 0.015), but without differences between groups (p > 0.05). No group (HIIT vs. MIIT), time (pre vs. post), or interaction effects (group vs. time) were found for RMR, body composition markers (fat mass, body fat percentage, lean mass), or body mass index – BMI (p > 0.05). In addition, MIIT induced a relatively high drop-out rate. CONCLUSIONS: This study suggested that the short-term (7-weeks) interval exercise training was effective for increasing aerobic fitness, and moderate-intensity intervals were as effective as high-intensity intervals. However, neither training format was effective for changing RMR, body composition variables, or BMI of women with overweight or obesity. Clinical trial ID: RBR-9jd7b7.